A comparative study of the efficacy and outcome of methylprednisolone and dexamethasone in moderate to severe COVID-19 disease - Praveen B Gautam,; Kumar, Arunesh; Kannojia, Babu Lal; Chaudhary, Rajendra (Asian Journal of Medical Sciences, 2021)
Background: COVID-19 disease is caused by severe acute respiratory syndrome corona virus 2 (SARS-CoV-2). In the first half of 2020 COVID-19 disease has already converted into a global pandemic. Many treatment options were explored through the world. Aims and Objectives: To compare the efficacy and outcome of methylprednisolone (MTP) and dexamethasone (DEXA) in moderate-to-severe COVID-19 disease. Materials and Methods: In this prospective study, a total of 140 moderate to severe COVID-19 patients were enrolled from 15 April to June 15, 2021. These patients were randomly allocated into two groups, 70 patients were received MTP 2 mg/kg/day for 3 days followed by 1.0 mg/kg/day for 3 days in divided doses while 70 patients received DEXA 8 mg/day in divided dose up to 10 days. Results: The mean age was 45.5 years in MTP group whereas 45.34 years in DEXA group. The clinical outcome in MTP group and DEXA group was assessed in terms of clinical improvement (92.85% vs. 81.42%), radiological improvement (82.85% vs. 68.57%), transfer to ICU (5.71 vs. 14.57%), needs of ventilatory support (2.85% vs. 8.57%) and mortality (7.14% vs. 18.57%) respectively. Conclusion: In this study, MTP demonstrated better outcome as compared to DEXA in COVID-19 patients.